ANALYSIS OF THE RELATIONSHIP OF THE EPHTHALITES AND THE SASSANIDS IN GERMAN HISTORIOGRAPHY - Ergasheva Diloromkhon (PEDAGOGS, 2025)
In this article, the relations between the Hephthalites, who had their place in the early medieval history of our country and were able to build a powerful state, with the Sassanids in Iran and the reasons for the wars between them are studied based on scientific research created in German, and finally it is concluded. Interest in the history of Iran is at the top of German historiography, and we can find answers to problematic questions in our own history through such research.